Prevalência de traumas faciais relacionados aos acidentes de motocicletas - Lonchi, Marília Fernanda Barboza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Trauma is very important to in contemporary society. According to the World Health Organization, the traumas are among the leading causes of death and morbidity in the world and have great importance since it presents emotional, functional and possibility of permanent deformities repercussions. A lot of lesions on the face due to the huge exposure and little protection in this region, which often results in severe injuries. The lesions of the head and face may represent 50% of all trauma deaths. Studies show that increasing the fleet of motorcycles in the country, is becoming a concern in view of vulnerability and exposure to risk of biker accidents in traffic. Specifically in relation to facial trauma, stress the importance of helmet as a preventive measure of maxillofacial and cranial injuries. The purpose of this study is: a) Conduct a literature review through the Virtual Health Library, indicating the descriptors of Terminology in health (DeCS) motorcycle accidents, Traumatology and Etiology. b) To study epidemiological data records from the Faculdade de Odontologia do campus de Araçatuba that had as casuist traumas caused by motorcycle accidents, whose patients were seen by the extension project entitled Surgical-Dental Care for patients with maxillofacial trauma Ambulatory and Hospital Level . After a series of 492 patients with a history of trauma by motorcycle, it was found that: a) 74% were male while 26% were female, b) the age of highest incidence was 21-30 years with 30 1%. Among the weekdays, motorcycle accidents occurred in greater numbers on Monday, with 18.1%. It was concluded from this work that motorcycle accidents occur more often in their most productive age of the individual. To cause severe face trauma, being commonly causing multiple injuries, motorcycle accidents generates high morbidity in the population needing to be prevented for political, economic and social development of a country

Os traumas apresentam grande importância na sociedade contemporânea. Segundo dados da Organização Mundial de Saúde, os traumas estão entre as principais causas de morte e morbidade no mundo e possuem grande importância uma vez que apresentam repercussões emocionais, funcionais e possibilidade de deformidades permanentes. A grande quantidade de lesões na face deve-se à enorme exposição e a pouca proteção desta região, o que acarreta frequentemente lesões graves. As lesões da cabeça e da face podem representar 50% de todas as mortes traumáticas. Estudos mostram que o aumento da frota de motocicletas, no país, vem se tornando motivo de preocupação, tendo em vista a vulnerabilidade e a exposição do motociclista ao risco dos acidentes no trânsito. Em relação especificamente aos traumas faciais, ressalta a importância do capacete como medida preventiva das lesões bucomaxilofaciais e cranianas. O presente trabalho teve como objetivos: a) Realizar um levantamento bibliográfico por meio da Biblioteca Virtual em Saúde, indicando os descritores da Terminologia em saúde (DeCS) Acidentes motociclísticos, Traumatologia e Etiologia. b) Estudar dados epidemiológicos em prontuários da Faculdade de Odontologia do campus de Araçatuba que tinham como casuísta os traumas causados por acidentes motociclísticos, cujos pacientes foram atendidos pelo projeto de extensão intitulado Atendimento Cirúrgico-Odontológico para pacientes com Traumatismo Bucomaxilofacial em Nível Ambulatorial e Hospitalar. Após uma casuística de 492 pacientes com histórico de trauma por motocicleta, verificou-se que: a) 74% eram do sexo masculino enquanto 26% eram do sexo feminino, b) a idade de maior incidência foi de 21 a 30 anos, com 30,1%. Dentre os dias da semana, os acidentes motociclísticos ocorreram em maior número...
Keywords: Motocicletas; Acidentes de trânsito; Saúde pública; Traumatismos faciais; Motorcycles